Current methods of studying of the proliferative activity in experiment - Ivanenko, T. V.; Abramova, T. V.; Kuzo, N. V.; Tyshchenko, S. V.; Іваненко, Тарас Васильович; Абрамова, Тетяна Вікторівна; Кузьо, Назар Володимирович; Тіщенко, Сергій Вікторович; Иваненко, Т. В.; Тищенко, Т. В.; Абрамова, Т. В.; Кузьо, Н. В. (ЗДМУ, 2014)
Aims. To analyze the contemporary scientifi c literature data about methods of determining of the proliferative activity, as well as the choice of an optimal method for its assessing in tissues with expected low proliferative activity. Methods and results. This is necessary to select an optimal method for assessing of the proliferative activity in tissues with expected low proliferative activity. The article gives a detailed analysis of the current literature, describes various methods of studying of the proliferative activity of tissues in experiment. Conclusion. Bromodeoxyuridine is a versatile and highly effective marker of DNA replication and cell proliferation, allowing carrying out a dynamic observation of the experiment, including tissues with expected low proliferative activity. It can be widely used in chronic experiments on small rodents, in the simulation of various pathologies and studying the effect of pharmaceuticals on the activity of proliferation. З метою аналізу сучасних даних про методи визначення проліферативної активності, а також для вибору оптимального методу для роботи із тканинами з низькою очікуваною проліферативною активністю дослідили новітні публікації в галузі. Встановили, що підрахунок мітотичного індексу має низьку чутливість і специфічність, а такі методи, як імуноферментний аналіз, імуноблотинг, імуногістохімічне дослідження, полімеразна ланцюгова реакція мають високу чутливість та інформативність, але лише імуногістохімічні дослідження дають змогу візуалізації з можливістю топічної діагностики. Це свідчить, що, незважаючи на переваги і відмінності кожного маркера проліферації, застосування бромдезоксіуридину дає можливість здійснювати динамічне оцінювання та визначення проліферативної активності клітин у тканинах із низькою проліферативною активністю через його кумулятивний ефект. С целью анализа современных данных о методах определения пролиферативной активности, а также для выбора оптимального метода для работы с тканями с низкой ожидаемой пролиферативной активностью исследовали новые публикации в отрасли. Установили, что подсчет митотического индекса имеет низкую чувствительность и специфичность, а такие методы, как иммуноферментный анализ, иммуноблоттинг, иммуногистохимическое исследование, полимеразная цепная реакция отличаются высокой чувствительностью и информативностью, но только иммуногистохимические исследования обеспечивают визуализацию с возможностью топической диагностики. Это свидетельствует, что, несмотря на преимущества и отличия каждого маркера пролиферации, применение бромдезоксиуридина позволяет проводить динамическую оценку и определение пролиферативной активности клеток в тканях с низкой пролиферативной активностью благодаря его кумулятивному эффекту.
Сучасні методи дослідження проліферативної активності в експерименті
Современные методы изучения пролиферативной активности в эксперименте
Keywords: cell proliferation; immunohistochemistry; PCNA; antigen Ki67; Bromodeoxyuridine; клітинна проліферація; імуногістохімія; бромдезоксіуридин; клеточная пролиферация; иммуногистохимия; бромдезоксиуридин